Role of Nox inhibitors plumbagin, ML090 and gp91ds-tat peptide on homocysteine thiolactone induced blood vessel dysfunction - Smith, Renee M; Kruzliak, Peter; Adamcikova, Zuzana; Zulli, Anthony (Clinical and experimental pharmacology & physiology, 2015)
Antioxidants have not reduced the burden of cardiovascular disease, and current evidence suggests a beneficial role of oxidative stress, via NADPH oxidase (Nox) upregulation, in endothelial function. Homocysteine thiolactone (HcyT) induces blood vessel dysfunction and this correlates with increased vascular oxidative stress. This study aimed to determine if pharmacological inhibition of Nox could impair HcyT induced blood vessel dysfunction. Abdominal aorta were excised from New Zealand White rabbits (n = 6), cut into rings and sequentially mounted in organ baths. Rings were preincubated with 0.55 μmol/L homocysteine thiolactone for 1 h, or combinations of putative Nox inhibitors (plumbagin for Nox4, gp91ds-tat for Nox2, and ML090 for Nox1), 30 min prior to the addition of HcyT, followed by a dose response curve to acetylcholine on phenylephrine preconstricted rings. Plumbagin, ML090 + gp91ds-tat and HcyT reduced responses to acetylcholine, and Plumbagin + Hcyt caused constriction to acetylcholine, which was normalised to plumbagin by ML090. Plumbagin + ML090 or plumbagin + gp91ds-tat completely impaired the effect of acetylcholine. ML090 inhibited the effect of HcyT on reduced response to acetylcholine, whereas gp91ds-tat had no effect. This study concludes that inhibition of Nox1 prevents, whereas inhibition of Nox4 worsens, acetylcholine induced blood vessel relaxation caused by HcyT, while Nox2 inhibition has no effect. However combinations of Nox inhibitors worsen acetylcholine induced blood vessel relaxation. These results suggest that there is cross-talk between Nox isoforms during physiological and pathophysiological processes.
Keywords: glykoproteiny; Animals; Rabbits; vztah mezi dávkou a účinkem léčiva; NADPH oxidase; naftochinony; Nox inhibitors; Enzyme Inhibitors; chinoxaliny; Naphthoquinones; Glycoproteins; endothelial dysfunction; NADPH-oxidasy; homocystein; Nox; Dose-Response Relationship, Drug; Male; aorta abdominalis; inhibitory enzymů; Quinoxalines; NADPH Oxidases; Homocysteine; králíci; zvířata; mužské pohlaví; Aorta, Abdominal